Activation of the DNA damage response pathway in the infected gastric tissue with Helicobacter pylori: a case-control study - Amiratabak Rajaei; Armin Ghameshlou; Reza Shirkoohi; Abbas Shakoori Farahani; Seyedeh Zohre Mirbagheri; Ronak Bakhtiari; Melika Sadat Haeri; Ali Rashidi-Nezhad; Masoud Alebouyeh (Journal of Infection in Developing Countries)
Introduction: Gastritis is among the most common human diseases worldwide. Although the involvement of Helicobacter pylori infection as a class I human carcinogen for gastric cancer progression is accepted, it is not well known how gastritis progression to atrophy and stomach cancer occurs. In this case-control study, the potential link of H. pylori infection with alteration in the transcription of genes involved in DNA Damage Response pathways was investigated among the patients with gastritis.